Lifestyle and health‐related risk factors and risk of cognitive aging among older veterans. (1st June 2014) - Yaffe, Kristine; Hoang, Tina D.; Byers, Amy L.; Barnes, Deborah E.; Friedl, Karl E.
Abstract: Lifestyle and health‐related factors are critical components of the risk for cognitive aging among veterans. Because dementia has a prolonged prodromal phase, understanding effects across the life course could help focus the timing and duration of prevention targets. This perspective may be especially relevant for veterans and health behaviors. Military service may promote development and maintenance of healthy lifestyle behaviors, but the period directly after active duty has ended could be an important transition stage and opportunity to address some important risk factors. Targeting multiple pathways in one intervention may maximize efficiency and benefits for veterans. A recent review of modifiable risk factors for Alzheimer's disease estimated that a 25% reduction of a combination of seven modifiable risk factors including diabetes, hypertension, obesity, depression, physical inactivity, smoking, and education/cognitive inactivity could prevent up to 3 million cases worldwide and 492, 000 cases in the United States. Lifestyle interventions to address cardiovascular health in veterans may serve as useful models with both physical and cognitive activity components, dietary intervention, and vascular risk factor management. Although the evidence is accumulating for lifestyle and health‐related risk factors as well as military risk factors, more studies are needed to characterize these factors in veterans and to examine the potential interactions between them.